The Blood Carboxyhemoglobin Levels of Firemen Occupationally Exposed to Carbonmonoxide - Güvendik, Gülin; Gündüzer, Serap; Tümtürk, Nuray (The Bulletin of Legal Medicine, 1997)
In this study, it has been aimed to investigate the blood- carboxyhemoglobin (COHb) levels of firemen occupationally exposed to CO. The derivative spectrophotometric method was used for the determination of carboxyhemoglobin saturation percent in blood samples. According to the result of the analysis: in the firemen, the mean COHb levels was found to be 5.93±0.25 % COHb for smokers (n*T5), 3.42 ± 0.23 %COHb for nonsmokers (n=5). In the control group, the mean COHb levels was found to be 5.48±0.22 % COHb for smokers (n=20), 1.26+0.05 % COHb for nonsmokers (n=20). Blood-COHb levels of firemen who smoke and control group were found significantly higher than the nonsmokers (p
Keywords: carbonmonoxide; carboxyhemoglobin; derivative spectrophotometry